Uncoupling of DNA Replication and Centrosome Duplication Cycles Is a Primary Cause of Haploid Instability in Mammalian Somatic Cells - Yoshizawa, Koya; Yaguchi, Kan; Uehara, Ryota (Frontiers in Cell and Developmental Biology, 2020)
Mammalian haploid somatic cells are unstable and prone to diploidize, but the cause of haploid instability remains largely unknown. Previously, we found that mammalian haploid somatic cells suffer chronic centrosome loss stemming from the uncoupling of DNA replication and centrosome duplication cycles. However, the lack of methodology to restore the coupling between DNA replication and centrosome duplication has precluded us from investigating the potential contribution of the haploidy-linked centrosome loss to haploid instability. In this study, we developed an experimental method that allows the re-coupling of DNA and centrosome cycles through the chronic extension of the G1/S phase without compromising cell proliferation using thymidine treatment/release cycles. Chronic extension of G1/S restored normal mitotic centrosome number and mitotic control, substantially improving the stability of the haploid state in HAP1 cells. Stabilization of the haploid state was compromised when cdk2 was inhibited during the extended G1/S, or when early G1 was chronically extended instead of G1/S, showing that the coupling of DNA and centrosome cycles rather than a general extension of the cell cycle is required for haploid stability. Our data indicate the chronic centriole loss arising from the uncoupling of centrosome and DNA cycles as a direct cause of genome instability in haploid somatic cells, and also demonstrate the feasibility of modulation of haploid stability through artificial coordination between DNA and centrosome cycles in mammalian somatic cells.